HETEROGENEOUS PHOTOCATALYTIC DEGRADATION OF 4-NITROPHENOL VIA TiO2, SURFACE-MODIFIED WITH SALICYLIC ACID - Kaya, Dila; San, Nevim (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2017)
The photocatalytic degradation of 4-nitrophenol (4-NP), an intoxicating substance even in minor concentrations, was carried out under UV light and visible light. The widely used photocatalyst, TiO2 has only limited ability to perform visible light induced photocatalytic reactions because of its band gap energy of 3.2 eV, which constitutes with the UV region of the spectrum. This attribute was tried to be given to the photocatalyst by modifying its surface with salicylic acid (SA), thus narrowing its band gap. It was revealed that a bidentate SA-TiO2 complex was formed on the TiO2 surface. In order to characterize the newly prepared surface-modified TiO2, a number of different methods were used including BET, FTIR, XRD and SEM. Through these methods, it was shown that the surface area increased while the crystal structure remained unchanged after the modification process. The photocatalytic activity of both bare and surface-modified TiO2 were examined by the degradation reaction of 4-NP in the presence of UV light and also sunlight. It was determined that the degradation reaction of 4-NP followed pseudo first order kinetics and 0.1%SA-TiO2 photocatalyst had a higher efficiency in terms of degradation than bare TiO2 under both UV light and sunlight.
Keywords: Photocatalytic degradation; titanium dioxide; 4-nitrophenol; surface modification; characterization; DOPED TIO2; WATER-TREATMENT; LIGHT; PHENOL; REDUCTION; MECHANISM; CO2; PHOTODEGRADATION; NANOPARTICLES; SUSPENSIONS; Environmental Sciences & Ecology